Incidence of Peripheral Arterial Disease and Its Association with Pulse Pressure: A Prospective Cohort Study - Mao, Yong; Huang, Yixiang; Yu, Haining; Xu, Peng; Yu, Guangping; Yu, Jinming; Zhan, Yiqiang (Frontiers in Endocrinology, 2017)
Background The association of pulse pressure and peripheral arterial disease (PAD) has seldom been examined using a prospective design. This study aimed to investigate the association of pulse pressure with PAD incidence in an elderly general population. Methods We utilized data from a cohort conducted in Beijing with additionally two-year follow-up time. PAD was defined as an ankle brachial index value < 0.9 in either leg. Cox proportional hazard regression model was used to quantify the magnitude of pulse pressure on PAD incidence. Results During a two-year follow-up time, 357 of 4201 (8.5%) participants developed PAD with 105 (6.9%) men and 252 (9.4%) women, respectively. After adjusting for baseline age, sex, body mass index, hypertension, diabetes, total cholesterol, and high density lipoprotein cholesterol, and smoking, the hazard ratio (HR) and 95% confidence interval (CI) for people with pulse pressure greater than 60 mmHg was 2.20 (1.53, 3.15) compared with those whose pulse pressure was less than 40 mmHg. A linear trend was observed for the association of pulse pressure with PAD. Conclusions Higher pulse pressure was associated with higher PAD incidence.